2021
DOI: 10.1111/os.13090
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Effect of Manual Reduction Combined with Internal Fixation Through Wiltse Paraspinal Approach in the Treatment of Thoracolumbar Fracture

Abstract: Objective: To evaluate the clinical outcome of manual reduction combined with pedicle fixation through Wiltse paraspinal approach (WPA) in the treatment of thoracolumbar fractures.Methods: From May 2017 to May 2019, 48 thoracolumbar fractures patients without neurological symptoms were enrolled in this study. Forty-eight patients were randomly divided into two groups based on the different surgical treatment. Group 1 was manual reduction combined with pedicle screw fixation through Wiltse paraspinal approach t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…Wiltse technique has become an increasingly popular minimally invasive approach in thoracolumbar surgery, [ 11 , 23 ] and has been reported to have the advantages of shorter operation time and hospital stay, less bleeding, lower cost, and lower incidence of complications. [ 24 ] In this study, intraoperative blood loss, postoperative drainage volume, and hospital stay of the Wiltse approach were significantly lower than those of classical group, indicating that the Wiltse technique is a relatively less invasive isthmus repair approach, which is consistent with other reports.…”
Section: Discussionmentioning
confidence: 99%
“…Wiltse technique has become an increasingly popular minimally invasive approach in thoracolumbar surgery, [ 11 , 23 ] and has been reported to have the advantages of shorter operation time and hospital stay, less bleeding, lower cost, and lower incidence of complications. [ 24 ] In this study, intraoperative blood loss, postoperative drainage volume, and hospital stay of the Wiltse approach were significantly lower than those of classical group, indicating that the Wiltse technique is a relatively less invasive isthmus repair approach, which is consistent with other reports.…”
Section: Discussionmentioning
confidence: 99%
“…The frame use is limited in non-operative acute fracture and cephalic traction force through cervical spine is poor in force quantity and direction adjustment. In 2018, Carlo et al [29] reported a 3-member manual reduction for acute burst fracture as a technical note; in 2021, Li et al [30] confirmed the effect of a 3-member manual reduction in acute spine fractures. However, a 3-member manual reduction is weak to correct chronic deformity following spine fracture because it cannot change the patient posture according to the deformity.…”
Section: Background Of Manual Reductionmentioning
confidence: 99%
“…He later modi ed his approach so that it could be applied in other lumbar diseases 10 . Different with traditional spine surgery which needs dissection of bilateral muscles, this approach does not need to intraoperatively strip the paraspinal muscles, and many advantages of this approach have been fveri ed, such as less trauma, less intraoperative bleeding, and quicker recovery 11 . Therefore, Wiltse approach has been widely used in the surgical treatment of spine surgeries, especially for elder patients who could not suffer the variety of complications including deep vein thrombosis, hypostatic pneumonia, and pressure sores.…”
Section: Introductionmentioning
confidence: 99%